2017
DOI: 10.1590/2179-8087.028013
|View full text |Cite
|
Sign up to set email alerts
|

Deformação Residual Longitudinal de Clones de Eucalyptus em Local Sujeito a Ventos

Abstract: RESUMODurante o desenvolvimento das árvores, esforços mecânicos são gerados com o intuito de mantê-la em equilíbrio e ereta em resposta a diversos fatores ambientais. Estes esforços são conhecidos como tensões de crescimento e variam na sua distribuição e intensidade nas diferentes espécies do gênero Eucalyptus. Portanto, objetivou-se avaliar a deformação residual longitudinal (DRL) e sua relação com as características de crescimento da árvore, propriedade física e mecânica da madeira de clones do híbrido Euca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, the significant relationship in E. dunnii was found only at the age of 15, and at the ages of 8, 13, and 19 it was not significant (Trugilho and Oliveira 2008). The relationships between LGS and BWD not significant in Eucalyptus were also presented in other studies (Beltrame et al 2012, Braz et al 2017. These results demonstrate the importance of BWD as a predictor parameter for LGS, but it shows attention according to the species and age evaluated.…”
Section: Adjusted Networkmentioning
confidence: 61%
See 4 more Smart Citations
“…However, the significant relationship in E. dunnii was found only at the age of 15, and at the ages of 8, 13, and 19 it was not significant (Trugilho and Oliveira 2008). The relationships between LGS and BWD not significant in Eucalyptus were also presented in other studies (Beltrame et al 2012, Braz et al 2017. These results demonstrate the importance of BWD as a predictor parameter for LGS, but it shows attention according to the species and age evaluated.…”
Section: Adjusted Networkmentioning
confidence: 61%
“…For example, in the LGS evaluation of 20 Eucalyptus grandis x E. urophylla hybrid clones, of 13 year sold, the LGS results varied between 0,037 mm and 0,116mm, with two statistically distinct groups and 11 clones in the group with the highest LGS (França et al 2017). In another study, the LGS found in ten hybrids of E. urophylla × E. grandis clones of approximately three years old, varied significantly between 0,060 mm and 0,116mm (Braz et al 2017). Unlike these studies, using the ANNs, it was possible to include the variable clone to predict LGS and this parameter was the most relevant (Figure 3).…”
Section: Adjusted Networkmentioning
confidence: 91%
See 3 more Smart Citations